Knowledge Levels of Prospective Science and Physics Teachers on Basic Concepts on Sound (Sample for Samsun City) - Bolat, Mualla; Sozen, Merve (Elsevier Science BV, 2009)
The study has been focused on the basis of determining the knowledge levels of prospective Science and Physics teachers on basic concepts on sound. The design of the research is a case study. The sampling consists of 92 students studying in Science and Physics teaching departments in the Faculty of Education at Ondokuzmayis University in the academic year of 2007/2008. Data were collected from by the means questionnaires. The data were analyzed both qualitatively and quantitatively. It was determined that the knowledge levels of prospective teachers on basic concepts were low and misconceptions were rather high. The results of study were interpreted comparing other studies in literature. (C) 2009 Elsevier Ltd. All rights reserved
World Conference on Educational Sciences -- FEB 04-07, 2009 -- Nicosia, CYPRUS
Keywords: Case Study; Primary School Curriculums; Sound; Concept; Knowledge Levels